Metacarpophalangeal Joint Impairment in Hand Osteoarthritis and Its Association With Mechanical Factors: Results From the Digital Cohort Osteoarthritis Design Hand Osteoarthritis Cohort. Issue 10 (16th July 2022) - Kouki, Inès; Tuffet, Sophie; Crema, Michel D.; Rousseau, Alexandra; Richette, Pascal; Dougados, Maxime; Berenbaum, Francis; Sellam, Jérémie; Courties, Alice
Abstract : Objective: To determine the prevalence, distribution, and characteristics associated with radiographic metacarpophalangeal (MCP) joint osteoarthritis (OA). Methods: This was a cross‐sectional study of baseline data from the Digital Cohort Osteoarthritis Design, a French monocentric cohort including patients with symptomatic hand OA. We evaluated the prevalence of radiographic MCP joint OA, defined as ≥2 MCP joints with a Kellgren/Lawrence score of ≥2. We compared the prevalence of MCP joint OA in the dominant and nondominant hands. Associations between radiographic MCP joint OA and patient characteristics were studied using univariable and multivariable logistic regression. Results: Radiographic MCP joint OA was present in 138 of the 425 patients (32.5%) but was not severe. Patients with MCP joint OA had a mean age of 69.2 ± 6.9 years, a body mass index of 25 ± 4.2 kg/m 2, and 86.2% were women. MCP joint OA was more frequent in the dominant hand and predominated at the first and second MCP joints. In the multivariable analysis, MCP joint OA was associated with older age (odds ratio [OR] 1.05 [95% confidence interval (95% CI) 1.01, 1.10] for each year), manual occupation (OR 3.74 [95% CI 1.21, 11.54]), scaphotrapezial OA (OR 2.18 [95% CI 1.27, 3.72]), and a high number of proximal interphalangeal joints with radiographic OA. MCP joint OA was not associated with metabolic syndrome or hand OA symptoms. Conclusion: In this cross‐sectional study using a hospital‐based hand OA cohort, radiographic MCP joint OA was frequent and associated with structural hand OA features rather than with symptom severity. Our results suggest that the involvement of MCP joints in hand OA is predominantly related to mechanical rather than systemic factors in this population.